New Zealand sea lion, Phocarctos hookeri , pup production—1995 to 2006 - B. L. Chilvers; I. S. Wilkinson; S. Childerhouse (New Zealand Journal of Marine and Freshwater Research, 2007)
The New Zealand sea lion (NZ sea lion), Phocarctos hookeri , is New Zealand's only endemic pinniped. Classified as vulnerable, it is one of the world's rarest pinnipeds. During the 1994/95 austral summer, a long‐term population‐monitoring programme of the Auckland Island colonies was initiated using standard procedures to estimate annual pup production. This paper reports the pup production estimates for the known NZ sea lion population over the last 12 years (1994/95 to 2005/06), and the variation in pup production estimates for the Auckland Islands. sixty‐four percent of the pup production for the entire NZ sea lion population occurred at Dundas Island, followed by Enderby Island (19%), and Figure of Eight Island (3%). These three sites are all at the Auckland Islands, making this area the primary breeding site for this species with 86% of all pup production occurring here. The remaining 14% were born at Campbell Island, with otago Peninsula representing